Telaah Kritis Akad Musyarakah Mutanaqisah - Muh Turizal Husein (Prodi Perbankan Syariah FAI UMT, 2019)
Since the opening of the MEA door in 2015 to 2020, it will be colored by a strategy competition and a tighter level of financial services business competition. Sharia Banking products based on partnerships with